Chiral circularly polarized crystalline luminescent material and synthetic method and application thereof
Through the self-assembly method of chiral organic phosphine ligand and metal halide, the brightness loss problem when the non-polarized light source is converted into a polarized light source is solved, and the synthesis process of chiral circularly polarized luminescent materials is simplified, achieving efficient and concise Synthesis process and excellent material properties.
Patent Information
- Application Number
- CN202411372552.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, conversion of non-polarized light sources into polarized light sources is often accompanied by large brightness losses, and the synthesis process of chiral circularly polarized luminescent materials is complicated, ligand modification is complicated, and the morphological uniformity is difficult to control.
The chiral circularly polarized crystal luminescent materials are synthesized by interfacial diffusion method or solvothermal method to achieve an efficient and concise synthesis process.
The obtained material has high asymmetric luminescence factor, excellent thermal stability and polymer processability, which solves the brightness loss problem, simplifies the synthesis process, and improves the morphological uniformity of the material.
Smart Images

Figure CN119431441A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a chiral circularly polarized crystalline luminescent material and a synthesis method and application thereof, belonging to the technical field of new materials. Background Art
[0002] As part of advanced visual perception, circularly polarized light has attracted much attention in the fields of three-dimensional display, bio-coding, and optical data processing. Nowadays, the pursuit of both high brightness and high asymmetry factor (g lum ) has become an inevitable trend of development. When using traditional physical methods to generate circularly polarized light, the non-polarized light source needs to pass through a polarizer and a quarter-wave plate in sequence, resulting in significant brightness loss. Therefore, the development of chiral luminescent materials that can directly generate CPL has become an effective way to solve this problem.
[0003] In recent years, CPL has made significant progress in the study of chiral lanthanide compounds, chiral organic small molecules and chiral polymers. At the same time, the orderly assembly of chiral luminescent elements can also significantly enhance the CPL signal and amplify g lum However, existing CPL materials still face challenges such as complex synthesis process of chiral organic molecules, cumbersome ligand modification, and difficulty in controlling morphological uniformity. Therefore, further exploring new high-efficiency chiral materials and enhancing CPL signals through the self-assembly of their luminescent elements remain important directions for future research. Summary of the invention
[0004] In order to solve the problem that the conversion from a non-polarized light source to a polarized light source is usually accompanied by a large brightness loss in the prior art of circularly polarized luminescence, and the problems that the synthesis process of chiral luminescent materials based on CPL in the prior art is complicated, the ligand modification is cumbersome, and the morphology uniformity is difficult to control. The present application provides an application of a crystalline material as a chiral circularly polarized crystalline luminescent material, wherein the crystalline material is formed based on the self-assembly of a chiral organic phosphine ligand and a metal halide, and the chiral circularly polarized crystalline luminescent material obtained by the efficient synthesis method has a high asymmetric luminescence factor, and due to the diphosphine chelating coordination effect of the chiral ligand, it can show excellent thermal stability and polymer processability, which not only solves the problem that the conversion from a non-polarized light source to a polarized light source is usually accompanied by a large brightness loss in the traditional physical method, but also realizes an efficient and concise synthesis process of the chiral luminescent material of CPL.
[0005] This application adopts the following technical solutions:
[0006] According to one aspect of the present application, a chiral circularly polarized crystalline luminescent material is provided, wherein the chiral circularly polarized crystalline luminescent material is in R configuration or S configuration;
[0007] The chemical formula of the R configuration is: (R-BINAP)2 M 2 X 2 Formula I;
[0008] The chemical formula of the S configuration is: (S-BINAP) 2 M 2 X 2 Formula II;
[0009] Among them, R-BINAP is R-(+)-1,1'-binaphthyl-2,2'-bis(diphenylphosphine), S-BINAP is S-(-)-1,1'-binaphthyl-2,2'-bis(diphenylphosphine), M + Representative Cu + 、Ag + At least one heavy metal ion, X - Represents Cl - Br - ,I - At least one halogen ion is present.
[0010] Optionally, the space group of the chiral circularly polarized crystalline luminescent material is a chiral space group;
[0011] The chiral space group is P4 3 2 1 2. P4 1 2 1 2. P6 3 At least one of;
[0012] The molecular formula in the crystalline structure of the transchiral circularly polarized crystalline luminescent material includes: 2 axially chiral phosphine ligands, 2 metal ions and two halogen ions; wherein the metal ion is in a four-coordinate mode, coordinated with two P atoms of an axially chiral phosphine ligand and two halogen ions to form a distorted tetrahedral spatial coordination configuration; the halogen ion is in a bridging mode, connecting the two metal ions.
[0013] Optionally, the molecular structure of the chiral circularly polarized crystalline luminescent material is a zero-dimensional structure.
[0014] Optionally, the chiral circularly polarized crystalline luminescent material is a micron-sized bulk single crystal or a nano-sized crystalline powder.
[0015] In the present application, the chiral circularly polarized crystalline luminescent material does not contain precious metals such as Au, Pt, and Pd.
[0016] Optionally, M + Cu + or Ag + , X - Cl - When the space group of the chiral circularly polarized crystalline luminescent material is P4 3 21 2 or P4 1 2 1 2, the unit cell parameters are α=β=γ=90°, Z=8;
[0017] M + Cu + or Ag + , X - Br - When the space group of the chiral circularly polarized crystalline luminescent material is P4 3 2 1 2 or P4 1 2 1 2, the unit cell parameters are α=β=γ=90°, Z=8;
[0018] M + Cu + or Ag + , X - For I - When the space group of the chiral circularly polarized crystalline luminescent material is P6 3 , the unit cell parameters are α=β=90°, γ=120°, Z=6.
[0019] Optionally, the chiral circularly polarized crystalline luminescent material has multi-peak emission, wherein the strongest double-peak emission is as follows:
[0020] M + Cu + When the emission peaks are 512±2nm and 545±2nm, the optimal excitation wavelength is 438±2nm. The strongest double peak emission is quite obvious, and the emission light is yellow-green emission.
[0021] M + Ag + When the emission peaks are 506±2nm and 543±2nm, the optimal excitation wavelength is 395±2nm. The strongest double peak emission is quite obvious, and the emission light is yellow-green emission.
[0022] Optionally, the chiral circularly polarized crystalline luminescent material has a thermal decomposition temperature greater than 390° C. and has good thermal stability.
[0023] Optionally, the asymmetry factor of the chiral circularly polarized crystalline luminescent material at 10-30° C. is -1.1×10 -4 ~18×10 -4 and -4.1×10 -4 ~23×10 -4 .
[0024] Optionally, the color coordinates of the chiral circularly polarized crystalline luminescent material are (0.33-0.35, 0.58-0.60).
[0025] Compounds at room temperature (R-BINAP) 2 Cu 2 I 2 The asymmetric luminescence factor of (denoted as R-CuI) is 2.9 / 5.5×10 -4 , compound (S-BINAP) 2 Cu 2 I 2 The asymmetric luminescence factor of (denoted as S-CuI) is -1.6×10 -3 and -4.1×10 -4 ; Compound (R-BINAP) 2 Ag 2 I 2 The asymmetric luminescence factor of (denoted as R-AgI) is -1.1 / 2.4×10 -4 , compound (S-BINAP) 2 Ag 2 I 2 The asymmetric luminescence factor of (denoted as S-AgI) is 1.8 / 2.4×10 -3 The compounds R / S-CuI and R / S-AgI have excellent machinability and can be mechanically mixed with functional polymers to prepare flexible luminescent films with bright luminescence.
[0026] The chiral circularly polarized crystalline luminescent material of the present invention exhibits excellent chiral fluorescence emission in the circularly polarized emission spectrum and has an excellent asymmetric luminescence factor.
[0027] According to another aspect of the present application, a method for preparing the chiral circularly polarized crystalline luminescent material is provided, which has simple steps, high purity and high yield of the obtained product, and is suitable for large-scale industrial production. The method comprises the following steps:
[0028] The chiral circularly polarized crystalline luminescent material is obtained by self-assembling the axial chiral organic phosphine ligand and the heavy metal ion halide by using an interface diffusion method or a solvothermal method;
[0029] The axially chiral organophosphine ligand is selected from 1,1'-binaphthyl-2,2'-bisdiphenylphosphine;
[0030] The heavy metal ion is selected from Cu + 、Ag + At least one of;
[0031] The halogen ion in the heavy metal ion halide is selected from Cl - Br- or I - At least one of .
[0032] Optionally, the interface diffusion method comprises:
[0033] In a reaction vessel, heavy metal ion halides are dissolved in a solution having a density greater than 1 g / cm 3 The saturated brine solution is used as the bottom solution;
[0034] Acetonitrile was added to the bottom solution as a buffer layer;
[0035] The axially chiral organophosphine ligand is dissolved in a liquid having a density less than 1 g / cm 3 The mixed solution is obtained by mixing the mixed solution with a benzene organic solvent and then added into the buffer layer, and allowed to stand to grow in the environment of the buffer layer to obtain the chiral circularly polarized crystalline luminescent material.
[0036] Optionally, the benzene-based organic solvent is selected from at least one of benzene, toluene and xylene.
[0037] Optionally, in the interfacial diffusion method, the feed ratio of the axially chiral organic phosphine ligand to the heavy metal ion halide is 1:1.5.
[0038] Optionally, the halide salt is selected from at least one of KCl, KBr, and KI.
[0039] Optionally, the standing time is 5 to 10 days.
[0040] Optionally, the interface diffusion method comprises the following steps:
[0041] (1) Dissolve metal halides CuCl, CuBr, CuI or AgCl, AgBr, AgI in a solution with a density greater than 1 g / cm 3 The bottom solution is a saturated aqueous solution of metal halide salts KCl, KBr, and KI. The reaction container can be a test tube, a homemade quartz tube, or a reaction bottle;
[0042] (2) adding acetonitrile to the bottom solution as a buffer layer;
[0043] (3) Dissolve the chiral ligand in a liquid with a density less than 1 g / cm 3 The mixture is then gently added to the buffer layer along the container wall;
[0044] (4) After being left to stand at room temperature for about a week, micron-sized block single crystals can be grown.
[0045] Optionally, the solvothermal method comprises:
[0046] The heavy metal ion halide and the axial chiral organic phosphine ligand are dissolved in a non-protonic polar solvent, heated for reaction under vacuum conditions, filtered, and allowed to stand to precipitate to obtain the chiral circularly polarized crystalline luminescent material.
[0047] Optionally, in the solvothermal method, the feed ratio of the axially chiral organic phosphine ligand to the heavy metal ion halide is 1:1.
[0048] Optionally, in the solvothermal method, the reaction conditions include: reaction temperature of 120-150° C., vacuum degree greater than or equal to 1 Torr, reaction time of 0.5-5 h, and stirring speed of 200-900 rpm.
[0049] Optionally, in the solvothermal method, the reaction time in the reaction conditions is selected from any value of 0.5h, 1h, 2h, 3h, 4h, 5h, or any range therebetween.
[0050] Optionally, in the solvothermal method, the stirring speed in the reaction conditions is selected from any value of 200 rpm, 250 rpm, 300 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 850 rpm, 900 rpm, or any range therebetween.
[0051] Optionally, in the solvothermal method, the reaction temperature in the reaction conditions is selected from any value of 120°C, 125°C, 135°C, 145°C, 150°C, or any range therebetween.
[0052] Optionally, the standing time is 5 to 10 days;
[0053] Optionally, the aprotic polar solvent is selected from at least one of N,N-dimethylformamide and acetonitrile.
[0054] Optionally, the solvothermal method comprises the following steps:
[0055] (1) Weighing the chiral organic ligand and the metal halide using a balance and transferring them into a flat-bottom flask;
[0056] (2) adding a magnetic stirrer and an aprotic solvent to the flat-bottom flask and evacuating the flask with a vacuum pump;
[0057] (3) Place the reaction bottle on a magnetic heating stirring table, heat and stir;
[0058] (4) After heating and stirring for a period of time, filter and collect the filtrate while hot, and crystals can be precipitated after standing. By controlling the reaction temperature, a crystalline material with a micro-nano structure can be obtained.
[0059] In the present application, the interfacial diffusion method or the solvothermal method is not strictly limited, and those skilled in the art can select appropriate reaction time, magnetic stirring speed and reaction temperature according to actual needs, so as to ensure that the reaction proceeds fully.
[0060] According to another aspect of the present application, there is provided an application of the above-mentioned chiral circularly polarized crystalline luminescent material in the fields of lighting display, 3D display, optical storage, optical anti-counterfeiting, and asymmetric synthesis.
[0061] The beneficial effects of this application include:
[0062] The chiral circularly polarized crystalline luminescent material provided in the present application is a crystalline material based on the self-assembly of chiral organic phosphine ligands and metal halides, which has high circularly polarized emission properties and good thermal stability and machinability. And both show double-peak emission, and the peak shape is Gaussian distribution, which are 512±2nm and 545±2nm (R / S-CuI), and 506±2nm and 543±2nm (R / S-AgI), respectively, and can maintain the high thermal stability of the crystalline material at a high temperature of 390°C. And it can form a flexible film by physical blending with functional polymers, and still have high-intensity luminescent properties, and its color coordinates are R / S-CuI (0.332, 0.603), R / S-AgI (0.345, 0.584). The preparation method of the chiral circularly polarized crystalline light-emitting material synthesized in the present application has simple steps and does not contain precious metals such as gold, palladium, and platinum. The obtained chiral circularly polarized crystalline light-emitting material has high purity, good crystallinity, and high yield, and is suitable for large-scale industrial production. The synthesized chiral circularly polarized crystalline light-emitting material shows important application prospects in the fields of 3D display, optical storage, optical anti-counterfeiting, and asymmetric synthesis. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 It is a schematic diagram of the crystal structure of sample R / S-CuI obtained in Example 1.
[0064] Figure 2 It is a schematic diagram of the crystal structure of sample R / S-AgI obtained in Example 1.
[0065] Figure 3 These are SEM morphology images of samples R / S-CuI and R / S-AgI obtained in Example 1.
[0066] Figure 4 The XRD diffraction theoretical patterns obtained by fitting the single crystal data of the samples R / S-CuI and R / S-AgI obtained in Example 1 and the experimentally measured XRD diffraction patterns thereof.
[0067] Figure 5 These are the thermal stability test results of samples R / S-CuI and R / S-AgI obtained in Example 1.
[0068] Figure 6 It is the photoluminescence experimental test spectrum of samples R / S-CuI and R / S-AgI obtained in Example 1, including the optimal excitation wavelength and the optimal emission wavelength.
[0069] Figure 7 These are the solid circular dichroism absorption spectra and solid UV-visible absorption spectra of the samples R / S-CuI and R / S-AgI obtained in Example 1.
[0070] Figure 8 It is the circularly polarized emission spectra of samples R / S-CuI and R / S-AgI obtained in Example 1.
[0071] Fig. 9 These are the CIE coordinates of the thin films of samples R / S-CuI and R / S-AgI obtained in Example 1 after mechanical processing. DETAILED DESCRIPTION
[0072] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0073] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels. Among them, R-(+)-1,1'-binaphthyl-2,2'-bisdiphenylphosphine and S-(-)-1,1'-binaphthyl-2,2'-bisdiphenylphosphine were purchased from Shanghai Bid Pharmaceutical Technology Co., Ltd.; metal halides, including CuCl, CuBr, CuI, AgCl, AgBr, AgI, and KCl, KBr, KI were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; toluene, benzene, N,N-dimethylformamide, acetonitrile, etc. were purchased from Sinopharm Holdings Co., Ltd., and deionized water was prepared in the laboratory.
[0074] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0075] Example 1 Preparation of R / S-CuI and R / S-AgI (solvothermal method)
[0076] R-CuI was synthesized as follows:
[0077] Turn on the electronic balance and preheat for 10 minutes; accurately weigh 2mmol organic ligand R-BINAP (1244mg) and 2mmol inorganic metal salt CuI (390mg), transfer to a 100mL flat-bottom round-bottom flask, then add 50mL N,N-dimethylformamide (DMF) and 16mL acetonitrile, and seal with a 90° exhaust funnel; to avoid oxidation of the reaction raw materials during the reaction, the reaction can be carried out under negative pressure, that is, the system is evacuated; transfer to a magnetic heating stirrer, heat at 130℃ for 2 hours, and control the speed at 880rpm. During the reaction, a faint yellow-green light can be observed from the system, indicating that the product has been formed. Filter while hot, and the yellow solid on the filter paper is the product. Wash with ethanol and dry. The product is 1548mg, yield: 94.7%; crystals can be precipitated in the filtrate.
[0078] S-CuI was synthesized as follows:
[0079] Turn on the electronic balance and preheat for 10 minutes; accurately weigh 2mmol organic ligand S-BINAP (1244mg) and 2mmol inorganic metal salt CuI (390mg), transfer to a 100mL flat-bottom round-bottom flask, then add 50mL N,N-dimethylformamide (DMF) and 16mL acetonitrile, and seal with a 90° exhaust funnel; to avoid oxidation of the reaction raw materials during the reaction, the reaction can be carried out under negative pressure, that is, the system is evacuated; transfer to a magnetic heating stirrer, heat at 130℃ for 2 hours, and control the speed at 880rpm. During the reaction, a faint yellow-green light can be observed from the system, indicating that the product has been formed. Filter while hot, and the yellow solid on the filter paper is the product. Wash with ethanol and dry. The product is 1495mg, and the yield is 91.5%; crystals can be precipitated in the filtrate.
[0080] R-AgI was synthesized as follows:
[0081] Turn on the electronic balance and preheat for 10 minutes; accurately weigh 2mmol organic ligand R-BINAP (1244mg) and 2mmol inorganic metal salt AgI (480mg), transfer to a 100mL flat-bottom round-bottom flask, then add 50mL N,N-dimethylformamide (DMF) and 16mL acetonitrile, and seal with a 90° exhaust funnel; to avoid oxidation of the reaction raw materials during the reaction, the reaction can be carried out under negative pressure, that is, the system is evacuated; transfer to a magnetic heating stirrer, heat at 125℃ for 3 hours, and control the speed at 900rpm. During the reaction, the system can be observed to turn into a yellow turbid suspension within 1 hour at the beginning, indicating that the product has been formed. Continue heating, the product dissolves, and a brown precipitate is produced. Filter while hot and collect the filtrate. After standing for 48 hours, crystals can be precipitated in the filtrate. Filter to obtain the product; the product is washed with ethanol and dried. The product is 985mg, and the yield is 57.1%.
[0082] S-AgI was synthesized as follows:
[0083] Turn on the electronic balance and preheat for 10 minutes; accurately weigh 2mmol organic ligand S-BINAP (1244mg) and 2mmol inorganic metal salt AgI (480mg), transfer to a 100mL flat-bottom round-bottom flask, then add 50mL N,N-dimethylformamide (DMF) and 16mL acetonitrile, and seal with a 90° exhaust funnel; to avoid oxidation of the reaction raw materials during the reaction, the reaction can be carried out under negative pressure, that is, the system is evacuated; transfer to a magnetic heating stirrer, heat at 125℃ for 3 hours, and control the speed at 900rpm. During the reaction, the system can be observed to turn into a yellow turbid suspension within 1 hour at the beginning, indicating that the product has been formed. Continue heating, the product dissolves, and a brown precipitate is produced. Filter while hot and collect the filtrate. After standing for 48 hours, crystals can be precipitated in the filtrate. Filter to obtain the product; the product is washed with ethanol and dried. The product is 866mg, and the yield is 50.2%.
[0084] Structural characterization of test example 1 samples
[0085] X-ray single crystal diffraction of compounds R / S-CuI and R / S-AgI was performed on a Rigaku FR-X micro-focus single crystal instrument using a Mo target and a Kα radiation source. The test temperature is 100K. The structure is analyzed by Olex2 1.2. The test results are as follows Figure 1 and 2 As shown, the compounds R / S-CuI and R / S-AgI are zero-dimensional molecular structures, containing two axially chiral phosphine ligands, two metal ions and two halogen ions; the metal ions are in a four-coordinate mode, coordinated with two P atoms of an axially chiral phosphine ligand and two halogen ions to form a distorted tetrahedral spatial coordination configuration; the halogen ions are in a bridging mode, connecting the two metal ions.
[0086] The microstructure of the compounds R / S-CuI and R / S-AgI can be obtained on a Hitachi ultra-high resolution field emission scanning electron microscope Regulus8100, where the tube voltage of the electron gun is 5kV. Figure 3 As shown in FIG. 1 , it can be seen from SEM that the compounds R / S-CuI and R / S-AgI are hexagonal prisms, and the particle size during the implementation process is about tens of microns.
[0087] X-ray powder diffraction phase analysis (XRD) of the ground compounds R / S-CuI and R / S-AgI was performed on a Rigaku SmartLab multifunctional X-ray diffractometer with a Cu target and a Kα radiation source. Test results such as Figure 4 Comparing the XRD diffraction theoretical pattern obtained by X-ray single crystal diffraction fitting with the XRD diffraction pattern measured by X-ray powder diffraction phase analysis, it can be seen that the XRD diffraction pattern obtained by single crystal data fitting is highly consistent with the XRD diffraction pattern measured experimentally, proving that the obtained sample is a sample of high purity and high crystallinity.
[0088] X-ray powder diffraction and X-ray single crystal diffraction results show that:
[0089] The compound R / S-CuI is a hexagonal P6 3 The space group has unit cell parameters of α=β=90°, γ=120°, Z = 6;
[0090] Compound R / S-AgI is a hexagonal P6 3 The space group has unit cell parameters of α=β=90°, γ=120°, Z=6.
[0091] The crystallographic data of samples R-CuI, S-CuI, R-AgI and S-AgI are shown in Table 1:
[0092]
[0093]
[0094] Test Example 2 Thermal Stability Test Experiment
[0095] The thermal stability of the compounds R / S-CuI and R / S-AgI was measured by thermogravimetric analysis (TGA) on a METTLER TOLEDO analyzer in a nitrogen atmosphere. 2 O 3 In a crucible at 10K min -1 Heating at a heating rate of Figure 5 As shown in the figure, the sample has good thermal stability and there is no obvious weight loss before 390 °C.
[0096] Test Example 3 Photoluminescence Performance Test Experiment
[0097] The photoluminescence performance test experiment of the compounds R / S-CuI and R / S-AgI is carried out, and the specific steps are as follows:
[0098] The instrument selected is the Edinburgh FLS1000 for photoluminescence performance testing, in which the excitation light source is a Xe lamp, and ultraviolet light of a specific excitation band can be selected through a filtering system. The excitation slit is 1mm and the receiving slit is 1mm.
[0099] The experimental spectrum of photoluminescence is shown in Figure 6 As shown. For the sample R / S-CuI, at the optimal excitation wavelength of 438nm, the sample exhibits a double-peak emission, with the emission being 512±2nm and 545±2nm respectively. For the sample R / S-AgI, at the optimal excitation wavelength of 395nm, the sample also exhibits a double-peak emission, with the emission being 506±2nm and 543±2nm respectively.
[0100] Test Example 4 Chiral Performance Test Experiment
[0101] The chirality of compounds R / S-CuI and R / S-AgI was tested, where the ground state chirality can be obtained through circular dichroism absorption spectra and compared with solid-state UV-visible absorption spectra; the excited state chirality can be obtained through circularly polarized emission spectra.
[0102] The instrument used to measure the chirality of the ground state was the MOS-500 from Bio-Logic, France. The solid-state pellet method was adopted, and the specific operation was as follows: 95 mg of spectrally pure KBr and 5 mg of the sample were weighed, fully ground and mixed, and pelletized at 20 MPa. During the test, the detector slit was 3 nm. In order to compare the position of the chromophore, the compounds R / S-CuI and R / S-AgI were also tested for solid UV-visible absorption spectra. The instrument used was the LAMBDA 365+ UV / visible spectrometer from PerkinElmer, USA. The specific operation was as follows: solid BaSO 4 As a reference, a certain amount of solid sample is weighed to keep the particle size in the sample consistent, and then the sample is placed in the measurement chamber of the UVR device, and then the device is started to automatically measure the UV-visible absorption of the solid sample. The test results are as follows Figure 7 As shown, it can be seen that the maximum range of the solid ultraviolet absorption spectrum corresponds to the maximum positive / negative Codon effect in the circular dichroism absorption spectrum, which can well explain the source of the ground state chirality of the chiral circularly polarized crystalline luminescent material.
[0103] The instrument used to measure the chirality of excited states is the CPL-300 model from JASCO of Japan. The solid-state measurement method is adopted. The specific operation is: disperse the sample as thinly as possible in the quartz sample cell, and let the excitation light be perpendicular to the sample so that the emitted light can pass through the detector slit. The test results are as follows: Figure 8 As shown, at room temperature the compound (R-BINAP) 2 Cu 2 I 2The asymmetric luminescence factor of (denoted as R-CuI) is 2.9 / 5.5*10 -4 , compound (S-BINAP) 2 Cu 2 I 2 The asymmetric luminescence factor of (denoted as S-CuI) is -1.6*10 -3 and -4.1*10 -4 ; Compound (R-BINAP) 2 Ag 2 I 2 The asymmetric luminescence factor of (denoted as R-AgI) is -1.1 / 2.4*10 -4 , compound (S-BINAP) 2 Ag 2 I 2 The asymmetric luminescence factor of (denoted as S-AgI) is 1.8 / 2.4*10 -3
[0104] Test Example 5 Luminescence Test Experiment after Machining
[0105] After grinding the compounds R / S-CuI and R / S-AgI and physically mixing them with PMMA, a relatively flexible polymer luminescent film can be obtained. The selected instrument is the Edinburgh FLS1000 for photoluminescence performance testing, where the excitation light source is a Xe lamp. The ultraviolet light of a specific excitation band can be selected through the filtering system. The excitation slit is 1mm and the receiving slit is 1mm.
[0106] By converting the experimental spectrum of photoluminescence, the color coordinate diagram can be obtained, such as Fig. 9 R / S-CuI and R / S-AgI can be mechanically mixed with functional polymers to prepare flexible luminescent films with bright luminescence, and their color coordinates are R / S-CuI (0.33, 0.60) and R / S-AgI (0.35, 0.58), respectively.
[0107] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A chiral circularly polarized crystalline luminescent material, characterized in that: The chiral circularly polarized crystalline luminescent material is in R configuration or S configuration; The chemical formula of the R configuration is: (R-BINAP)2M2X2 Formula I; The chemical formula of the S configuration is: (S-BINAP)2M2X2 Formula II; Among them, R-BINAP is R-(+)-1,1'-binaphthyl-2,2'-bis(diphenylphosphine), S-BINAP is S-(-)-1,1'-binaphthyl-2,2'-bis(diphenylphosphine), M + Representative Cu + 、Ag + At least one heavy metal ion, X - Represents Cl - Br - ,I - At least one halogen ion is present.
2. The chiral circularly polarized crystalline luminescent material according to claim 1, characterized in that: The space group of the chiral circularly polarized crystalline luminescent material is a chiral space group; The chiral space group is at least one of P43212, P41212, and P63; Preferably, the molecular structure of the chiral circularly polarized crystalline luminescent material is a zero-dimensional structure.
3. The chiral circularly polarized crystalline luminescent material according to claim 1, characterized in that: M + Cu + or Ag + , X - Cl - When the space group of the chiral circularly polarized crystalline luminescent material is P43212 or P41212, the unit cell parameter is α=β=γ=90°, Z=8; M + Cu + or Ag + , X - Br - When the space group of the chiral circularly polarized crystalline luminescent material is P43212 or P41212, the unit cell parameter is α=β=γ=90°, Z=8; M + Cu + or Ag + , X - For I - When the space group of the chiral circularly polarized crystalline luminescent material is P63, the unit cell parameter is α=β=90°, γ=120°, Z=6.
4. The chiral circularly polarized crystalline luminescent material according to claim 1, characterized in that: The chiral circularly polarized crystalline luminescent material has multi-peak emission, wherein the strongest double-peak emission is as follows: M + Cu + When , the emission peaks are 512±2nm and 545±2nm, and the optimal excitation wavelength is 438±2nm; M + Ag + When , the emission peaks are 506±2nm and 543±2nm, and the optimal excitation wavelength is 395±2nm.
5. The chiral circularly polarized crystalline luminescent material according to claim 1, characterized in that: The thermal decomposition temperature of the chiral circularly polarized crystalline luminescent material is greater than 390°C.
6. The chiral circularly polarized crystalline luminescent material according to claim 1, characterized in that: The asymmetry factor of the chiral circularly polarized crystalline luminescent material at 10-30°C is -1.1×10 -4 ~18×10 -4 and -4.1×10 -4 ~23×10 -4 .
7. The chiral circularly polarized crystalline luminescent material according to claim 1, characterized in that: The color coordinates of the chiral circularly polarized crystalline luminescent material are (0.33-0.35, 0.58-0.60).
8. The method for preparing a chiral circularly polarized crystalline luminescent material according to any one of claims 1 to 7, characterized in that: The steps include: The chiral circularly polarized crystalline luminescent material is obtained by self-assembling the axial chiral organic phosphine ligand and the heavy metal ion halide by using an interface diffusion method or a solvothermal method; The axially chiral organophosphine ligand is selected from 1,1'-binaphthyl-2,2'-bisdiphenylphosphine; The heavy metal ion is selected from Cu + 、Ag + At least one of; The halogen ion in the heavy metal ion halide is selected from Cl - Br - or I - At least one of .
9. The preparation method according to claim 8, characterized in that: The interface diffusion method includes: In a reaction vessel, heavy metal ion halides are dissolved in a solution having a density greater than 1 g / cm 3 The saturated brine solution is used as the bottom solution; Acetonitrile was added to the bottom solution as a buffer layer; The axially chiral organophosphine ligand is dissolved in a liquid having a density less than 1 g / cm 3 The mixed solution is obtained by mixing the mixed solution with a benzene organic solvent and then added to the buffer layer, and allowed to stand to grow in the environment of the buffer layer to obtain the chiral circularly polarized crystalline luminescent material; Preferably, in the interfacial diffusion method, the feed ratio of the axially chiral organic phosphine ligand to the heavy metal ion halide is 1:1.5; Preferably, the halide salt is selected from at least one of KCl, KBr, and KI; Preferably, the standing time is 5 to 10 days; Preferably, the solvothermal method comprises: Dissolving a heavy metal ion halide and an axially chiral organic phosphine ligand in a non-protonic polar solvent, heating to react under vacuum conditions, filtering, standing, and precipitating to obtain the chiral circularly polarized crystalline luminescent material; Preferably, in the solvothermal method, the feed ratio of the axially chiral organic phosphine ligand to the heavy metal ion halide is 1:1; Preferably, in the solvothermal method, the reaction conditions include: reaction temperature of 120 to 150° C., vacuum degree greater than or equal to 1 Torr, reaction time of 0.5 to 5 h, and stirring speed of 200 to 900 rpm; Preferably, the standing time is 5 to 10 days; Preferably, the aprotic polar solvent is selected from at least one of N,N-dimethylformamide and acetonitrile.
10. Application of the chiral circularly polarized crystalline luminescent material according to any one of claims 1 to 7 in the fields of lighting display, 3D display, optical storage, optical anti-counterfeiting, and asymmetric synthesis.
Citation Information
Patent Citations
Preparation method of bis(diphenylphosphine)-palladium dichloride chiral catalyst
CN111039989A
Perovskite crystal, circular polarization luminescent material thereof, preparation method and application
CN116396242A
CuP2N type cuprous complex and fluorescence sensing of CuP2N type cuprous complex to pyridine
CN117186121A
Binaphthylamine derivative as well as preparation method and application thereof
CN117209440A
Emitter material for oleds
WO2023079035A1
Cited By
Chiral silver-palladium nano-cluster as well as preparation method and application thereof
CN119775325A